Rapid Prototyping of a Hybrid PV–Wind Generation System Implemented in a Real-Time Digital Simulation Platform and Arduino (2019)
: The growing penetration of generation systems based on renewable energy in electric power systems is undeniable. These generation systems have many benefits, but also many challenges from the technical point of view. One of the biggest problems in the case of solar photovoltaic (PV) and wind energy is the intermittency of the raw material, thus hybrid generation systems that contain both sources are being used to complement electric power generation. To analyze the problems of this type of hybrid generation systems, it is necessary to develop models and test systems that allows to study their dynamic behavior. Reported in this paper is the implementation of a full hybrid PV–wind generation system model in a real-time digital simulation platform, and the development of the electronic converter controls. These controllers were implemented in digital devices (Arduino Due) and connected to the simulation platform to test their performance in real-time. In addition, the procedure followed for the development and implementation of the controllers is presented. The proposed test system can be used in renewable energy integration studies and the development of new control strategies.